659 LEFT ATRIAL MYXOMA IN A PATIENT PRESENTING WITH ACUTE CORONARY SYNDROME: IS EMBOLISM THE PATHOPHYSIOLOGICAL MECHANISM?. (15th December 2022) - Oliva, Carlo-agostino; Falcone, Stefania; Morello, Matteo; Ghiringhelli, Sergio; Provasoli, Stefano; Tamborini, Claudio; De Ponti, Roberto
Abstract: Background: Cardiac myxomas, though uncommon, do represent the most frequent primary cardiac neoplasms in human beings. Their clinical presentation is mainly due to flow obstruction, cytokines hyperincretion or embolism. Coronary embolism related to the tumor is a rare finding. Here we describe the case of a left atrial cardiac myxoma with an acute coronary syndrome presentation. Case presentation: A 71 year-old woman referred for chest pain, nausea and vomit. On the previous few months she had developed exertional dyspnea and fatigue. No prior history of cardiovascular diseases was reported. The 12-lead ECG showed no significant alterations. Troponin T values were elevated (224 ng/L, normal assay threshold <14 ng/L). Transthoracic echocardiogram displayed left apical akynesia and a bulky left atrial mass protruding through the mitral valve in systole. Coronary angiography showed complete distal occlusion of the left anterior descending (LAD) coronary artery. Thromboaspiration allowed for the retrieval of small-sized non-thrombotic material in the culprit vessel, without angiographic signs of atherosclerotic disease, thus hinting at the embolic nature of LAD occlusion. The patient was then referred to the surgical theatre for removal of the atrial mass, which showed a 4.3×3.4×3.2 cm translucid, lobulated and gelatinous neoformation attached to the interatrial septum via a 1.5×1.2 cm stalk. The mass was surgically removed and the interatrial septum was repaired with a pericardium patch. Hystology was consistent with left atrial myxoma. The hospitalization course was uneventful. Conclusion: We reported a case of acute coronary syndrome due to left atrial myxoma. Coronary embolization induced by a cardiac myxoma is rare; however, it should be suspected in patients presenting with myocardial infarction without adjunctive coronary risk factors.